Implementasi Bermain Caklingking Angka dalam Meningkatkan Kemampuan Berhitung Anak Usia 5-6 Tahun di TK Az-Zakyyah Desa Kace - Dewi, Lisa Puspa (ICEJ : Islamic Childhood Education Journal, 2024)
The main problem of this research regarding the numeracy skills of children aged 5-6 years is that there are still errors in recognizing the numbers 6 and 9, 1 and 7. And there are children who do not focus when learning addition and subtraction and are still lacking. The aim of the research is to answer the problem formulation regarding the implementation of the caklingking game in improving the numeracy skills of early childhood class 2B at Az-Zakyyah Kindergarten, Kace Village. The type of research used in this research is descriptive qualitative. Descriptive qualitative research is describing something that happens in the field obtained from observations, interviews and documentation. The research data source was taken from primary data sources consisting of 1 school principal, 2 teachers at Az-Zakyyah Kindergarten in Kace Village and secondary data sources. The data analysis techniques used in the research are data reduction, data presentation and drawing conclusions. The implementation of playing caklingking numbers in improving numeracy skills has 3 stages, namely 1) Planning, namely the teacher understands the kindergarten activity program, makes RPPH and RPPM. 2) Implementation, namely the teacher prepares the number caklingking game, the teacher arranges the child’s position, the teacher explains how to play the number caklingking game. 3) Evaluation, namely, the teacher makes a scale of developmental achievements, anecdotal notes and work results. Thus, it can be concluded that the results of the implementation of the number caklingking game in improving children’s numeracy skills in counting/mentioning numbers 1-20, recognition of the concept of numbers has seen improvement from the research results, namely that children develop according to expectations (BSH) and develop very well (BSB) even though there are 3 Children are starting to develop (MB) because they still need to be reminded and helped by teachers.